Modern aragonite formation at near-freezing conditions in an alpine cave, Carnic Alps, Austria - Spötl, Christoph; Fohlmeister, Jens (Chemical geology, 2016)
Aragonite is a common mineral in caves hosted in dolomitic bedrock, and in particular in those from warm climate regions. It is much less common in cold caves, such as in the Alps, where the vast majority of speleothems consist of low-Mg calcite. Here we report the occurrence of modern aragonite at very low temperatures, the first of its kind from an alpine cave. In the interior part of Obstanser Eishöhle, a high-alpine cave containing perennial ice in its near-entrance zone, aragonite forms stalactites and flowstones, which coexist with calcite and locally also hydromagnesite. Precipitation of aragonite occurs at saturation indices between 0.4 and 0.6 at 1.0±0.4°C. Modern 230Th dates of the youngest aragonite deposits demonstrate that aragonite formation is an ongoing process. δ13C values are high and overlap with those of the host rock. A comparison between δ18O values of aragonite and drip water showed that modern aragonite formation does not occur at isotopic equilibrium. Surprisingly, no radiocarbon “bomb peak” was detected in these speleothems, despite their young age. In addition, these samples are characterized by extremely high reservoir ages between 8800 and 10,100yr, the highest ever reported for a speleothem worldwide. These data are best reconciled with a model of karst dissolution largely decoupled from the soil zone. Oxidation of disseminated pyrite in the dark gray host rock gives rise to acidic solutions driving carbonate dissolution. The dolomitic nature of the bedrock, prior calcite precipitation and ventilation-enhanced degassing leads to high Mg/Ca ratios in the drip water favoring aragonite formation. These in-situ observations confirm previous findings that temperature is not the dominant control on calcite versus aragonite formation in caves. They also suggest that ancient aragonite speleothems should be examined carefully and ideally be compared to coeval calcite samples prior to interpreting their stable isotope data in terms of environmental/climatic changes.
Gesehen am 12.05.2020